Women in the Boardroom and Firm Financial Performance: Evidence from the Nasdaq OMX Helsinki firms - Ruuska, Mira (My University, 2017)
This study investigates the relationship between female board members in publicly listed companies and firm financial performance. The cross-sectional data set involves 82 publicly listed companies from Nasdaq OMX Helsinki stock exchange in year 2016. The study is conducted as an OLS regression analysis with board diversity as an explanatory variable and firm size, board size, industrial sector and performance measure at different time point as control variables. The empirical analysis investigates the relationship between Return on Asset, Return on Equity and gender diversity within the board of directors. This study contributes to previous literature by conducting the research on latest data from Finnish companies. As far as one is concerned, there are no published literature that would investigate the relationship between female board members and financial performance of the Nasdaq OMX Helsinki firms. Empirical findings of this study suggest a positive and statistically significant relationship between firm financial performance and board diversity. Moreover, empirical evidence suggests that financial performance measures of the sample firms are positively correlated.
Keywords: Corporate governance; firm performance; board of directors; gender diversity; return on asset; return on equity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|